Investigations on feeding techniques of dielectric resonator antenna at 26 GHz - Irfan Ali; Mohd Haizal Jamaluddin; Abinash Gaya (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, Microstrip slot aperture and Microstrip line feeding techniques of dielectric resonator antenna are investigated and examined at 26 GHz for 5G applications. The dielectric resonator has a dielectric constant of 10 and etched on Rogers RT/Duroid 5880 substrate having a thickness of 0.254mm and relative permittivity of 2.2. The proposed structures are optimized and simulated using the commercial software CST Microwave studio. The effect of feeding techniques on the bandwidth, radiation efficiency, gain, VSWR and radiation pattern are also examined and analysed. The return loss, bandwidth, gain, radiation efficiency, VSWR and radiation pattern are presented and compared based on the excitation method employed for the studied DRA. The simulated results show that the microstrip slot aperture provides good performance and is suitable for 5G applications.